Léčba chronické bolesti u zánětlivých revmatických onemocnění - Suchý, David; Lejčko, Jan (Vnitrni lekarstvi, 2018)
Chronic pain is a common health problem related to most of inflammatory rheumatic disorders. It is pain that has persisted for at least 3 month and cannot be fully relieved by standard pain medication. 40-60 % of patients do not have adequate relief of their pain. Paramount in the management of chronic pain patients is assessment of the pain and its impact on physical and psychosocial functioning. Multidisciplinary and multimodal approach is of vital importance. Non-steroidal anti-rheumatic drugs (NSA) have been used mainly due to their strong analgesic effect, especially in the treatment of acute pain as well as their anti-inflammatory effect in the treatment of chronic i pain. Long-term systemic administration of NSA may be associated with a number of serious side effects, which significantly limit NSA use in long term therapy. Due to opiophobia, opioids are insufficiently used treatment modality. Knowledge about pain and its management, as well as an awareness of barriers to effective pain therapy, are important not only for pain specialists but also primary care physicians.Key words: chronic pain - non-steroidal antirheumatic drugs - opiophobia - opioids - pain assessment - paracetamol - rheumatoid arthritis.
Keywords: chronická bolest; Humans; Chronic Pain; opioidní analgetika; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; revmatoidní artritida; Arthritis, Rheumatoid; lidé; Analgesics, Opioid